2006
DOI: 10.1074/jbc.m506646200
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Apolipoprotein E4 and Amyloid β Peptide

Abstract: We previously demonstrated that apolipoprotein E4 (apoE4) potentiates lysosomal leakage and apoptosis induced by amyloid ␤ (A␤) peptide in cultured Neuro-2a cells and hypothesized that the low pH of lysosomes accentuates the conversion of apoE4 to a molten globule, inducing reactive intermediates capable of destabilizing cellular membranes. Here we report that neutralizing lysosomal pH with bafilomycin or NH 4 Cl abolished the apoE4 potentiation of A␤-induced lysosomal leakage and apoptosis in Neuro-2a cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(59 citation statements)
references
References 75 publications
0
57
0
2
Order By: Relevance
“…In cultured Neuro-2a cells, we showed that apoE4 enhances A␤-induced lysosomal leakage and apoptotic cell death to a much greater extent (2-to 4-fold) than apoE3 (74,127).…”
Section: Apoe4 Potentiation Of A␤-induced Lysosomal Leakage and Apoptmentioning
confidence: 85%
“…In cultured Neuro-2a cells, we showed that apoE4 enhances A␤-induced lysosomal leakage and apoptotic cell death to a much greater extent (2-to 4-fold) than apoE3 (74,127).…”
Section: Apoe4 Potentiation Of A␤-induced Lysosomal Leakage and Apoptmentioning
confidence: 85%
“…Previous reports have suggested that the lysosomal accumulation of A␤42 may play an important role in neuronal cell death and that the loss of lysosomal membrane impermeability is involved in A␤42 pathogenesis (22,23,68,69), but what is essential for the A␤42-induced lysosomal damage remains to be shown. We confirmed the view that A␤42 applied extracellularly leads to fluorescence diffusion of endocytosed punctate Lucifer Yellow and lysosomal enzyme leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with alkalizing drugs, such as chloroquine and BafA1, obviously ameliorated lysosome damage and cell death. A recent publication by Ji et al (68,69) reported that apoE4 and A␤42 might work in concert at lower pH to increase the susceptibility of lysosomes to disruption. They also pointed out that the question of whether the apoE4/A␤42 complex or the two molecules, independently, destabilize the membranes still remains to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms may be that the expression of autophagy‐related genes decreases with (Omata, Lim, Akao, & Tsuda, 2014), as well as ApoE4 induces membrane disruption of lysosomes, release of lysosomal enzymes, leading to dysfunction of autophagic machinery (Ji, Müllendorff, Cheng, Miranda, & Huang, 2006). …”
Section: Pathological Association Between Autophagic Pathways and Alzmentioning
confidence: 99%